2011
DOI: 10.1021/ie101252w
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Extraction and Separation Process for Coffee Beans with Supercritical CO2 and Water

Abstract: The aim of this work was to develop a new process for extraction and separation of polar and nonpolar compounds from natural materials using supercritical CO2 (SCCO2) in water. In this work, chlorogenic acid and caffeine from coffee beans were used as model compounds of polar and nonpolar compounds, respectively. Extraction and separation were conducted in three types of semicontinuous extractors with different sizes and flow types of CO2 and water. The effect of temperature and pressure in the separation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…Azevedo et al (2008) showed that the addition of ethanol and isopropyl alcohol as co-solvents increases the yield of CQAs from green coffee beans. Experiments of Machmudah et al (2011) revealed that not only the addition of a polar solvent but also the way of conducting the extraction affects the yield. These researchers proved that the counter-current extraction in flow mode is more effective compared to both batch and co-current extraction with CO 2 .…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…Azevedo et al (2008) showed that the addition of ethanol and isopropyl alcohol as co-solvents increases the yield of CQAs from green coffee beans. Experiments of Machmudah et al (2011) revealed that not only the addition of a polar solvent but also the way of conducting the extraction affects the yield. These researchers proved that the counter-current extraction in flow mode is more effective compared to both batch and co-current extraction with CO 2 .…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…Afterwards, the role of ethanol was investigated, tempting the different percentages those are: 5; 7.5; and 10%, with CO 2 flow rate of 6 ml/min.. In this research, the results of pressure, temperature, and supercritical CO 2 flow rate of two macro algae on extraction yield were examined, and the experimental and model results were compared [11]. Table 1 and table 2 show the experimental data that were compared with the model of broken and intact cells.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional solid‐liquid extraction requires the use of expensive and hazardous organic solvents, harmful both for living beings and the environment . Supercritical CO 2 extraction overcomes this obstacle providing high‐quality extracts while reducing the toxicity associated with the solvents and shortening the processing time .…”
Section: Introductionmentioning
confidence: 99%